KEAKTIFAN BELAJAR SISWA KELAS 3 SDN HANDIL BAKTI MELALUI PENERAPAN MODEL PEMBELAJARAN KOOPERATIF - Muhammad Hafiz Fadhillah; Luqie Sabila; Nur Azkiyah; Novia Alifah Mawardah; Ahmad Suriansyah; Wahdah Refia Rafianti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the learning activeness of third-grade students at SDN Handil Bakti through the implementation of a cooperative learning model. The low level of student participation in asking questions, answering questions, and interacting during lessons served as the background of this research. The method employed was a descriptive qualitative approach, with data collected through classroom observations, interviews with teachers and students, and a review of learning-related documents. The results indicate that the implementation of the STAD (Student Teams Achievement Divisions) type of cooperative learning model significantly increased students’ learning activeness. Of the 28 students, 75% began to actively ask questions and participate in discussions after the second week of implementation. The frequency of student questions increased from 3–4 questions to 12–15 questions per session. Students’ physical, mental, cognitive, and emotional engagement also improved, as reflected in their enthusiasm during group discussions, their ability to collaboratively solve problems (85.7% of groups were successful), and their active involvement in manipulating instructional materials (80% of students). However, several challenges were identified, including the dominance of higher-achieving students and time constraints. Strategies such as clear role distribution within groups and consistent teacher guidance proved effective in addressing these obstacles. Overall, this study strengthens the evidence that cooperative learning is a relevant and effective approach to enhancing learning activeness at the elementary school level.